Creative learning for inclusion : creative approaches to meet special needs in the classroom - Sellman, Edward (London : Routledge, 2012)
'Creative Learning to Meet Special Needs explores the crucial role that creativity can play in inclusive education. It outlines a number of practical challenges faced by teachers working in both mainstream and special schools and the conceptual issues which frame successful learning for young people with special needs. It practically shows teachers examples of how to use creativity in the curriculum, and also how to engage with and support the learning of pupils with special educational needs in a way that will substantially impact their school experiences and later lives. This book collects together six accounts of creative approaches to meet special needs. These case studies are written by teachers and creative practitioners, each one considering a different theme: - the importance of location and context - early years - sustainability of practice - the assessment of learning - creative uses of technology - student participation. Describing the different ways in which a creative approach can help pupils with SEN access the curriculum, with activities and practical materials for teachers, this book will explain: - Why creativity is central to making the curriculum accessible - How to use personalised learning with pupils with SEN - How to promote achievements and motivation through creative experiences - How the curriculum can be extended and represented in innovative ways for pupils with SEN - How to use interactive methods of teaching and alternative methods of communication Creative Learning to Meet Special Needs is an invaluable guide for all those involved in teaching and engaging young people with special needs'-- Provided by publisher.
Includes bibliographical references and index.
Keywords: Children with disabilities -- Education; Creative ability -- Study and teaching; Creative teaching; Inclusive education